2019
DOI: 10.21203/rs.2.12976/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HPV E6/E7 mRNA test for the detection of high grade cervical intraepithelial neoplasia (CIN2+): A systematic review

Abstract: Background: Genital infection with certain types of Human papillomavirus (HPV) is a major cause of cervical cancer globally. For early detection of premalignant dysplasia, evidences are coming out on the usefulness of HPV E6/E7 mRNA test as a potential tool compared with cytology and HPV DNA testing. Taking into account shortage of compiled data on this field, the aim of this systematic review was to describe the latest diagnostic performance of HPV E6/E7 mRNA testing to detect high grade cervical lesions (CIN… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…In the present review, women were tested for the HPV E6/E7 mRNA, miRNA (miR-9), p16INK4a / ki-67, DNA methylation, SCC-Ag, M-CSF, and VEGF predominately secondary to having positive cervical cytology, and/or VIA and/or positive HPV DNA test. Overexpression of E6 / E7, p16 /ki-67, miR-9, SCC-Ag, M-CSF, VEGF proteins, or JAM3, SOX1, and L1 genes following infection with HPV can be detected based on their elevated levels in plasma, serum, Cervical scraping, or tissue as predictors of increased risk of cervical cancer progression [29,32,54,55]. The proportion of CIN2+ varied between 13.7 and 88.4%, reflecting the diverse spectrum of cervical pathologies of the participants employed in articles we included.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present review, women were tested for the HPV E6/E7 mRNA, miRNA (miR-9), p16INK4a / ki-67, DNA methylation, SCC-Ag, M-CSF, and VEGF predominately secondary to having positive cervical cytology, and/or VIA and/or positive HPV DNA test. Overexpression of E6 / E7, p16 /ki-67, miR-9, SCC-Ag, M-CSF, VEGF proteins, or JAM3, SOX1, and L1 genes following infection with HPV can be detected based on their elevated levels in plasma, serum, Cervical scraping, or tissue as predictors of increased risk of cervical cancer progression [29,32,54,55]. The proportion of CIN2+ varied between 13.7 and 88.4%, reflecting the diverse spectrum of cervical pathologies of the participants employed in articles we included.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of CIN2+ varied between 13.7 and 88.4%, reflecting the diverse spectrum of cervical pathologies of the participants employed in articles we included. From experimental studies, it has been established that woman exposed to HPV E6/E7 mRNA following infection with HPV have higher risk of progressing to highgrade cervical neoplasia due to the integration of viral DNA sequence into host genome causing loss of E2 tumor suppressor gene that regulates expression of E6 and E7 oncogenes [13,54,56]. Consequently, this results in overexpression of the two oncogenes which become useful in evaluating risk of cervical carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review report by Burger et al shows that the sensitivity of HPV DNA detection is 70%-100% and the speci city is only 28%-56%, while the Aptima mRNA detection approved by the FDA for clinical use in cytology is ASC-US population, the sensitivity is 91%-95% and the speci city is 42-61% [21] . Another research showed that the sensitivity is 91.4% and the speci city is 46.2% of Aptima mRNA [22] . The second-generation Hybrid Capture Technology (HC-2) speci cation showed that the sensitivity, speci city, positive predictive value, and negative predictive value of high-grade cervical intraepithelial lesions and cervical cancer were diagnosed in patients with Pap smear diagnosed as ASC-US were: 93.0%, 61.1%, 17.2%, 99.0%.…”
Section: Resultsmentioning
confidence: 97%
“…Protein expression biomarkers include p16INK4a/ki-67, SCC-Ag, M-CSF and VEGF. However, not all these biomarkers are suitable for the diagnosis of HIV-associated cervical cancer [ 44 , 45 , 46 ].…”
Section: The Genetics Of Molecular Biomarkersmentioning
confidence: 99%